FIVE-TIER FORMAT MISCONCEPTION DIAGNOSTIC INSTRUMENT: SYSTEMATIC LITERATURE REVIEW - Triani, Elza; Fahlani, Ilham (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2024)
This study aims to identify the types of misconceptions in physics learning and their causes through a systematic literature review. Misconceptions, triggered by internal factors such as incorrect initial understanding and external factors such as inappropriate learning resources, are a major challenge in physics learning. The five-level diagnostic instrument offers an effective solution to comprehensively analyze misconceptions by evaluating students' answers, the reasons behind them, and their beliefs about the answers. A bibliometric analysis of 317 articles (2015–2024) using VOSviewer showed three main themes: students' understanding, diagnostic tool development, and teaching effectiveness. The findings showed that students' misconceptions often occur in abstract physics concepts, such as motion and force. The five-level instrument allows for deeper identification than other instruments, helping teachers to carry out more targeted learning interventions. The results of this study confirm that the use of the five-level diagnostic instrument significantly improves students' understanding of physics concepts and reduces misconceptions. In addition, this study highlights the need to develop more effective diagnostic instruments to support better physics learning processes